2018
DOI: 10.1108/nfs-09-2017-0181
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest malpractices in fresh fruits and vegetables: food safety and health issues in India

Abstract: Purpose Fruits and vegetables, being good source of energy, health promoting and protecting compounds with unique taste and flavor, are attracting consumers since ages. These horticultural produces start deterioration just after harvest; therefore, their proper storage is must during transportation and storage to retain maximum quality parameters and for good market value. Best storage conditions are required to prevent growth of micro flora and to maintain the nutritional values of harvested produce. Retailer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 19 publications
0
25
0
3
Order By: Relevance
“…The full potential of antioxidants from plant origin (including mango kernel) is yet to be explored owing to their unavailability, high extraction cost, and the seasonal nature of most plant commodities. At present, there is a shift to natural antioxidants due to serious health concerns posed by synthetic antioxidants; regrettably, synthetic antioxidants tend to be cheaper compared to natural ones (Maisuthisakul & Gordon, 2009;Panghal et al, 2018). Dorta, Lobo, and González (2012) reported that mango kernel extract (12% in yield) possessed a high antioxidant activity.…”
Section: Antioxidant Compoundsmentioning
confidence: 99%
“…The full potential of antioxidants from plant origin (including mango kernel) is yet to be explored owing to their unavailability, high extraction cost, and the seasonal nature of most plant commodities. At present, there is a shift to natural antioxidants due to serious health concerns posed by synthetic antioxidants; regrettably, synthetic antioxidants tend to be cheaper compared to natural ones (Maisuthisakul & Gordon, 2009;Panghal et al, 2018). Dorta, Lobo, and González (2012) reported that mango kernel extract (12% in yield) possessed a high antioxidant activity.…”
Section: Antioxidant Compoundsmentioning
confidence: 99%
“…Traditionally, P. speciosa are used to treat hypertension, diabetes, hypoglycemic, antitumor, antimicrobial, headache, and kidney problems [5]. These health benefits are accounted to the presence of several phytochemical compounds such as terpenoids, polyphenols, flavonoids, alkaloids, saponins, steroids, tannins, and phytosterols demonstrating good antioxidant activity [6][7][8]. Extracts from the seeds and pods also have high content of total polyphenol, phytosterol, and flavonoids [9].…”
Section: Traditional Usesmentioning
confidence: 99%
“…Followed by TTL, 1,2,4,6,-tetrathiepane, and 1,2,4,5,6-pentathiepane are found in higher amount in P. speciosa. These compounds are donor of dithiocetal (C-S-C) which is used as antifungal effect for kidney and urinary bladder [8,13,20]. Polysulfide compounds found in P. speciosa exhibits antimicrobial and antibacterial properties [35], and thiazolidine exert anticancer property [15].…”
Section: Organosulfide Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial colors and dyes used in food industries to manipulate quality may lead to carcinogenicity, hypersensitivity, behavioral effects on prolonged consumption and thus not considered as safe [57]. The pod extract produces polyphenolic, betalain dye and chlorophyll content which is used in dyeing.…”
Section: Dye Productionmentioning
confidence: 99%